Induction of Tolerance to Therapeutic Proteins With Antigen-Processing Independent T Cell Epitopes: Controlling Immune Responses to Biologics - Schurgers, Evelien; Wraith, David C. (Frontiers in Immunology, 2021)
The immune response to exogenous proteins can overcome the therapeutic benefits of immunotherapies and hamper the treatment of protein replacement therapies. One clear example of this is haemophilia A resulting from deleterious mutations in the FVIII gene. Replacement with serum derived or recombinant FVIII protein can cause anti-drug antibodies in 20-50% of individuals treated. The resulting inhibitor antibodies override the benefit of treatment and, at best, make life unpredictable for those treated. The only way to overcome the inhibitor issue is to reinstate immunological tolerance to the administered protein. Here we compare the various approaches that have been tested and focus on the use of antigen-processing independent T cell epitopes (apitopes) for tolerance induction. Apitopes are readily designed from any protein whether this is derived from a clotting factor, enzyme replacement therapy, gene therapy or therapeutic antibody.